COVID-19 and telehealth in the intensive care unit setting: a survey - Nelson, Sarah E.; Steuernagle, Jon; Rotello, Leo; Nyquist, Paul; Suarez, Jose I.; Ziai, Wendy (BMC health services research, 2022)
Background Coronavirus disease (COVID-19) has led to changes in how healthcare is delivered. Here, through the administration of surveys, we evaluated telehealth use and views in US intensive care units (ICUs) during the pandemic. Methods From June 2020 to July 2021, voluntary, electronic surveys were provided to ICU leaders of Johns Hopkins Medical Institution (JHMI) hospitals, members of the Neurocritical Care Society (NCS) who practice in the US, and Society of Critical Care Medicine (SCCM) members practicing adult medicine. Results Response rates to our survey were as follows: 18 of 22 (81.8%) JHMI-based ICU leaders, 22 of 2218 (1.0%) NCS members practicing in the US, and 136 of 13,047 (1.0%) SCCM members. COVID-19 patients were among those cared for in the ICUs of 77.7, 86.4, and 93.4% of respondents, respectively, in April 2020 (defined as the peak of the pandemic). Telehealth technologies were used by 88.9, 77.3, and 75.6% of respondents, respectively, following the start of COVID-19 while only 22.2, 31.8, and 43.7% utilized them prior. The most common telehealth technologies were virtual meeting software and telephone (with no video component). Provider, nurse, and patient communications with the patient’s family constituted the most frequent types of interactions utilizing telehealth. Most common reasons for telehealth use included providing an update on a patient’s condition and conducting a goals of care discussion. 93.8–100.0% of respondents found telehealth technologies valuable in managing patients. Technical issues were noted by 66.7, 50.0, and 63.4% of respondents, respectively. Conclusions Telehealth use increased greatly among respondents following the start of COVID-19. In US ICUs, telehealth technologies found diverse uses during the pandemic. Future studies are needed to confirm our findings.